Fabricating niosomal-PEG nanoparticles co-loaded with metformin and silibinin for effective treatment of human lung cancer cells - Salmani-Javan, Elnaz; Jafari-Gharabaghlou, Davoud; Bonabi, Esat; Zarghami, Nosratollah (Frontiers in Oncology, 2023)
Background: Despite current therapies, lung cancer remains a global issue and requires the creation of novel treatment methods. Recent research has shown that biguanides including Metformin (MET) and Silibinin (SIL) have a potential anti-cancer effect. As a consequence, the effectiveness of MET and SIL in combination against lung cancer cells was investigated in this study to develop an effective and novel treatment method.Methods: Niosomal nanoparticles were synthesized via the thin-film hydration method, and FE-SEM, FTIR, AFM, and DLS techniques were used to evaluate their Physico-chemical characteristics. The cytotoxic effects of free and drug-loaded NPs, as well as their combination, on A549 cells, were assessed using the MTT assay. An apoptosis test was used while under the influence of medication to identify the molecular mechanisms behind programmed cell death.Using a cell cycle test, it was determined whether pharmaceutical effects caused the cell cycle to stop progressing. Additionally, the qRT-PCR technique was used to evaluate the levels of hTERT, BAX, and BCL2 gene expression after 48-hour medication treatment.In the cytotoxicity assay, the growth of A549 lung cancer cells was inhibited by both MET and SIL. Compared to the individual therapies, the combination of MET and SIL dramatically and synergistically decreased the IC50s of MET and SIL in lung cancer cells.Furthermore, the combination of MET and SIL produced lower IC50 values and a better antiproliferative effect on A549 lung cancer cells. Real-time PCR results showed the expression level of the hTERT, and BCL-2 were significantly reduced in lung cancer cell lines treated with MET and SIL compared to single treatments. (P<0.001).It is anticipated that the use of nano niosomal formed MET and SIL would improve lung cancer treatment outcomes and improve the therapeutic efficiency of lung cancer cells.